2016
DOI: 10.1111/efp.12322
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pathogenicity of marine Cladosporium spp. towards mangroves

Abstract: Summary Mangroves play an important role in coastal ecosystems. In this work, Cladosporium spp were isolated from a natural mangrove environment in Zhanjiang Bay, Guangdong Province, China. Ninety‐one isolates were obtained and identified as Cladosporium cladosporioides, C. colocasiae, C. oxysporum, C. perangustum, C. sphaerospermum, C. tenuissimum and C. uredinicola. Forty‐two isolates were selected and tested for pathogenicity towards mangroves. The results showed that pathogenic isolates were found on Avice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Fusarium solani and Metschnikowia bicuspidata are a threat for shrimp and prawn aquaculture (Baker et al 2009, Hatai et al 2012; both species have already been reported in apparently healthy sponges (Baker et al 2009, Paz et al 2010, Bolaños et al 2015. Concerning plants, Cladosporium perangustum (isolated from marine water) showed pathogenic activity against mangrove leaves under laboratory conditions (Liu et al 2016). These fungi are probably opportunistic pathogens, not properly able to affect healthy organisms, like the sponges of the present studies; however, further studies will be necessary to better understand their ecological role.…”
Section: Mycobiotamentioning
confidence: 61%
“…Fusarium solani and Metschnikowia bicuspidata are a threat for shrimp and prawn aquaculture (Baker et al 2009, Hatai et al 2012; both species have already been reported in apparently healthy sponges (Baker et al 2009, Paz et al 2010, Bolaños et al 2015. Concerning plants, Cladosporium perangustum (isolated from marine water) showed pathogenic activity against mangrove leaves under laboratory conditions (Liu et al 2016). These fungi are probably opportunistic pathogens, not properly able to affect healthy organisms, like the sponges of the present studies; however, further studies will be necessary to better understand their ecological role.…”
Section: Mycobiotamentioning
confidence: 61%